Chemistry of fossil fuels and biofuels - Schobert, Harold H., 1943- (New York : Cambridge University Press, 2013)
'Focusing on today's major fuel resources - ethanol, biodiesel, wood, natural gas, petroleum products and coal - this book discusses the formation, composition and properties of the fuels, and the ways in which they are processed for commercial use. It examines the origin of fuels through natural processes such as photosynthesis and the geological transformation of ancient plant material; the relationships between their composition, molecular structures and physical properties; and the various processes by which they are converted or refined into the fuel products appearing on today's market. Fundamental chemical aspects such as catalysis and the behaviour of reactive intermediates are presented and global warming and anthropogenic carbon dioxide emissions are also discussed. The book is ideal for graduate students in energy engineering, chemical engineering, mechanical engineering and chemistry, as well as professional scientists and engineers'--
Machine generated contents note: 1. Fuels and the global carbon cycle; 2. Catalysis, enzymes and proteins; 3. Photosynthesis and the formation of polysaccharides; 4. Ethanol; 5. Plant oils and biodiesel; 6. Composition and reactions of wood; 7. Reactive intermediates; 8. Formation of fossil fuels; 9. Structure-property relationships among hydrocarbons; 10. Composition, properties and processing of natural gas; 11. Composition, properties and classification of petroleum; 12. Petroleum distillation; 13. Heterogeneous catalysis; 14. Catalytic routes to gasoline; 15. Middle distillate fuels; 16. Thermal processing in refining; 17. Composition, properties and classification of coals; 18. The inorganic chemistry of coals; 19. Production of synthesis gas; 20. Gas treatment and shifting; 21. Uses of synthesis gas; 22. Direct production of liquid fuels from coal pyrolysis; 23. Carbonization and coking of coal; 24. Carbon products from fossil and biofuels; 25. Carbon dioxide.
Includes bibliographical references and index.
Keywords: Fossil fuels -- Analysis; Biomass energy; Energy crops -- Composition; Fuelwood crops -- Composition